PENGEMBANGAN VIDEO ANIMASI BERBASIS GENERATIVE AI DALAM MENINGKATKAN PEMAHAMAN SISWA PADA PELAJARAN PAI KELAS 1 SD - Nurhabibah Nurhabibah; Zulfitria Zulfitria (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The integration of Generative Artificial Intelligence (Generative AI) into education provides opportunities to create more interactive and engaging learning media for elementary school students. However, the development of Generative AI-based instructional media remains limited, highlighting the need for innovative learning resources that enhance learning quality. This study aimed to develop, assess the feasibility, and evaluate the effectiveness of Generative AI-based animated videos as a learning medium for first-grade students at SD Budi Luhur, Tangerang City. The study employed the Research and Development (R&D) method using the ASSURE model and involved 30 first-grade students. The development process followed the ASSURE stages, including learner analysis, stating objectives, selecting methods, media and materials, utilizing media and materials, requiring learner participation, and evaluation and revision. Data were collected through expert validation, user response questionnaires, and learning achievement tests, then analyzed using descriptive quantitative techniques. The results indicated that the developed animated video was highly valid based on expert assessment, received excellent user responses, and effectively improved students' learning outcomes, as indicated by an N-gain score of 0.83 (high category). Therefore, the Generative AI-based animated video is suitable for use as a learning medium to support learning in elementary schools. ABSTRAK Pemanfaatan teknologi Generative Artificial Intelligence (Generative AI) dalam pembelajaran memberikan peluang untuk menghadirkan media yang lebih interaktif dan menarik bagi siswa sekolah dasar. Namun, pengembangan media pembelajaran berbasis Generative AI masih terbatas sehingga diperlukan inovasi yang mampu meningkatkan kualitas pembelajaran. Penelitian ini bertujuan untuk mengembangkan, menguji kelayakan, dan mengevaluasi efektivitas video animasi berbasis Generative AI sebagai media pembelajaran bagi siswa kelas I SD Budi Luhur Kota Tangerang. Penelitian menggunakan metode Research and Development (R&D) dengan model ASSURE yang melibatkan 30 siswa kelas I. Pengembangan media dilaksanakan melalui tahapan analisis karakteristik peserta didik, perumusan tujuan pembelajaran, pemilihan metode, media, dan materi, pemanfaatan media, pelibatan aktif peserta didik, serta evaluasi dan revisi. Data dikumpulkan melalui validasi ahli, angket respons pengguna, dan tes hasil belajar, kemudian dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa video animasi yang dikembangkan memenuhi kriteria sangat valid berdasarkan penilaian ahli, memperoleh respons pengguna yang sangat baik, serta efektif meningkatkan hasil belajar siswa dengan nilai N-gain sebesar 0,83 yang termasuk kategori tinggi. Dengan demikian, video animasi berbasis Generative AI layak digunakan sebagai media pembelajaran untuk mendukung pembelajaran di sekolah dasar.